A sharing economy market system for private EV parking with consideration of demand side management. (1st January 2020) - Xu, Fangyuan; Chen, Xujie; Zhang, Miao; Zhou, Ya; Cai, Yanpeng; Zhou, Yang; Tang, Ruixin; Wang, Yifei
Abstract: Sharing economy leads to a series of revolutions in various industries, which increases the efficiency of assets utilization and reduces redundant products. Parking space sharing is a typical presentation of sharing economy. With the rapid development of electric vehicle (EV), shared parking with EVs brings a large storage resources with dynamic entry and exit behaviours for microgrid. This paper proposes a new market framework for shared parking space with EVs. This framework provides chances for microgrid or aggregator to utilize the EVs' storages in the demand side management (DSM). DSM in microgrid will optimize their costs by modifying EVs' charging/discharging behaviours. The benefits earned from DSM will be shared to car owners as well. Moreover, the proposed compensational matching module will use the shared DSM benefit to compensate the price gap between cars and car owners, indicating that DSM on sharing car space can provide more parking chances. A numerical study on practical data is used to verify the model. Results show that the proposed framework can not only reduce the power cost of microgrid and renting fee of cars, but also promote more chances of parking. Highlights: A shared parking market system with electric vehicles' demand side management is proposed. The complex and dynamics behaviors of electric vehicles are considered in DSM. The framework shares the parking spaces to car owners and brings the DSM benefit. A compensational module is designed to compensate the price gap for more parking spaces. A modified interior point optimization with gradient projection and climb-up-space is developed.